دور الرقابة الإدارية في مكافحة الفساد في شركة طرطوس لصناعة الإسمنت ومواد البناء " دراسة حالة " (Latakia University Journal - Economic and Legal Sciences Series, 2016)
تمثِّل ظاهرة الفساد الإداري ظاهرة عالمية شديدة الانتشار ذات جذور عميقة تأخذ أبعاداً واسعة تتداخل فيها عوامل مختلفة يصعب التمييز بينها، وتختلف درجة شموليتها من مجتمع إلى آخر. كما أنَّ الآثار المدمِّرة والنتائج السلبية لتفشِّي هذه الظاهرة تطال كل مقوِّمات الحياة لعموم أبناء الشعب، فتهدر الثروات وتعرقل أداء المسؤوليات وإنجاز الوظائف والخدمات. هذا يعني أن ظاهرة الفساد تشكِّل منظومة تخريب وإفساد وتأخير في عملية البناء والتقدُّم ليس على المستوى الإداري والمالي فقط، بل في الحقل السياسي والاقتصادي والاجتماعي والثقافي. مما يحتِّم إنشاء نظام رقابي فعَّال مستقل مهمَّته الإشراف ومتابعة الممارسات التي تتم من قبل الوزراء والموظَّفين العاملين في كل وزارة ومؤسَّسة.من هنا جاء هذا البحث للوقوف على دور الرقابة الإدارية في مكافحة الفساد في الشركات الصناعية في سورية (وكمثال عن هذه الشركات تمَّ تطبيق البحث على شركة طرطوس لصناعة الإسمنت ومواد البناء) من جهة ولتقييم أهم المسبِّبات الرئيسة للفساد وهي الضعف والقصور في الإجراءات والعمليات الرقابية من جهة ثانية. حيث تطرَّقت الباحثة إلى مفهوم الرقابة الإدارية وأهميّتها، وإلى ظاهرة الفساد الإداري ومسبِّباتها، وكيفيَّة التصدِّي لها، بالإضافة إلى أهميَّة الرقابة في مكافحة الفساد. كما توصَّلت الباحثة في نهاية هذا البحث إلى مجموعة من الاستنتاجات وأهمّها: لا تنسجم أساليب الرقابة الإدارية المستخدمة في شركة طرطوس لصناعة الإسمنت ومواد البناء مع الأساليب الكمية الحديثة ووسائل الرقابة التحليلية المتناغمة مع التطورات التكنولوجية وثورة المعلوماتية.في نهاية البحث تقدَّمت الباحثة بمجموعة من المقترحات والتوصيات وكان أهمُّها: ضرورة معالجة العوامل التي تساهم في تدنِّي مستوى الرقابة، والمتمثِّلة في ضعف التخطيط الفعَّال لإجراءات الرقابة، وغياب المساءلة والعدالة التي يمكن أن تكون سبباً في انتشار الفساد.The administrative corruption phenomenon is global and is widely and deeplyrooted that takes a broad dimensions with various factors that are difficult to distinguish between them. The degree of coverage varies from one society to another. The devastating effects and consequences of this phenomenon affects all life of all people, wastes resourcesand impede the fulfillment of responsibilities, functions and services, and thus constitute a system of sabotage and delay in construction and development process, not on the administrative and financial levels, but also political, economic, social and cultural levels, necessitating an effective independent regulatory system controls and follows-up practices of Ministers and officials in all ministries and institutions.Hence this research examines the role of administrative control in the fight against corruption in Syria industry companies (example about this companies Tartous companyfor Cement And Building materials Industry)in side and to evaluate the most important causes of corruption and the weakness and shortcomings in the regulatory procedures and processes in other side. The researcher addressed the concept of administrative supervision and its importance to the phenomenon of corruption and its causes, and how to address them, as well as the importance of control in the fight against corruption. The researcher concluded at the end of this research to a group of important conclusions: there are differences between control methods which have used tocombat corruption in Tartous Companyfor Cement And Building materials Industry, and the modern quantity methods and modern analyses control methods.In the end the researcher put forward a set of proposals and recommendations, including: the need to address the factors that contribute to the low level of control, and poor planning for effective control procedures, and lack of accountability and justice that could be the cause of corruption.